Cadmium concentrations in the soil-plant system in coffee crops in two production systems - Oliva, Manuel (2021)
Concern about cadmium content in the soils of crop-producing areas has been increasing in recent years. In the present investigation, the concentration of cadmium in the soil, leaf and fruit system was evaluated in coffee farms under two production systems, organic and conventional, in the district of Omia, Amazonas region, Peru. Soils, leaves and fruits were sampled and the cadmium concentration was measured by spectrophotometry, then a comparison was made by means of an analysis of variance; the soils were also characterized according to their pH, organic matter and electrical conductivity characteristics and a Pearson correlation was carried out. As a result, the concentration of cadmium in the soil, leaf and fruit systems did not exceed the Maximum Permissible Limits (MPL) stipulated by the Peruvian Ministry of the Environment, obtaining higher values in the soil with 0.72 mg kg-1, while lower values were found in the fruit with 0.1 mg kg-1. Comparing the concentration in two production systems, it is observed that both in soil and leaves the highest concentration is in the organic system, while in fruits the highest concentration is in the conventional system. In addition, a significant and positive correlation was found between the cadmium content of the soils and their physicochemical characteristics such as pH and percentage of organic matter. In conclusion, the results obtained do not exceed the LPM, so cadmium concentration in this crop is not considered a problem.